English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

what are the steps

2007-10-10 08:19:55 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

y=(m+b)/(mx-b) multiply both side by (mx-b)

y(mx-b)=m+b
ymx - yb =m + b add yb to both sides
ymx = yb + m + b divide by my

x= (yb+m+b)/my

2007-10-10 08:27:26 · answer #1 · answered by mbdwy 5 · 0 0

Y=(m+b)/ (mx-b) <-- I assumed you meant this. If so, then
Y(mx-b) = m+b <-- Did cross multiplication to get this
Ymx -Yb = m+b <-- Removed parentheses
Ymx = m +b +Yb <-- Moved Yb to other side & changed sign
x = (m+b+Yb)/mY <-- Division property

2007-10-10 15:30:15 · answer #2 · answered by ironduke8159 7 · 0 0

y= (m+b) /( mx-b)
Switch mx-b and y,
mx-b = (m+b) /y
Move -b to the other side, and divide both sides by m,
x = (1/m)[ (m+b) /y + b] = (m+b+by)/(my)

2007-10-10 15:24:18 · answer #3 · answered by sahsjing 7 · 0 0

fedest.com, questions and answers